2012
DOI: 10.1136/bmjqs-2012-000803
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic errors in the intensive care unit: a systematic review of autopsy studies

Abstract: Our data suggest that as many as 40,500 adult patients in an ICU in USA may die with an ICU misdiagnoses annually. Despite this, diagnostic errors receive relatively little attention and research funding. Future studies should seek to prospectively measure the prevalence and impact of diagnostic errors and potential strategies to reduce them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
153
6
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(169 citation statements)
references
References 62 publications
7
153
6
3
Order By: Relevance
“…The study conducted by Winters B et al [14] also showed that infections (41%) were most common class I errors, which includes pneumonia and aspergillosis. In our study, commonly missed infections were of tuberculosis and pneumonia.…”
Section: Discussionmentioning
confidence: 92%
“…The study conducted by Winters B et al [14] also showed that infections (41%) were most common class I errors, which includes pneumonia and aspergillosis. In our study, commonly missed infections were of tuberculosis and pneumonia.…”
Section: Discussionmentioning
confidence: 92%
“…CI: confidence interval recent systematic review of autopsy studies suggested that major misdiagnoses occurred in 6% of ICU deaths and estimated that 40,500 adult patients in the United States may die with an ICU misdiagnosis annually. (18) In conclusion, our study has found a high frequency of distractions in the ICU, and adds new information on the characterisation and risks for major distractions. Distractions frequently lead to interruptions while working, and junior doctors in our study were particularly susceptible to major distractions.…”
Section: Discussionmentioning
confidence: 99%
“…This forces some of the members to update the others through external communication means (e.g., phone). Since not all members are always reachable, the resident will need to communicate the information in a timely manner, thus adding to the existing cognitive load often experienced in the ICU [8]. To address this first problem, we envision a smart system where the resident can notify other clinicians as required, enhancing the ability for everyone to remain mobile.…”
Section: Problem Spacementioning
confidence: 99%
“…In sum, the completion of all the action-items requires an awareness of a patients' condition and other team member's contribution to the plan of action for the day. Equally significant and impactful to a patient's care and recovery is clear and regular communication and collaboration between the critical care team members [3,8,10].…”
Section: Problem Spacementioning
confidence: 99%